Infestations by the bagworms Metisa plana and Pteroma pendula for the period 1986-2000 in major oil palm estates managed by Golden Hope Plantation Berhad in peninsular Malaysia - Ho Cheng Tuck, Ibrahim Yusof, Khoo Khay Chong, (N/A, 2011)
Infestations by the bagworms Metisa plana and Pteroma pendula for the period 1986-2000 in major oil palm estates managed by Golden Hope Plantation Berhad in peninsular Malaysia by Ho Cheng Tuck, Ibrahim Yusof, Khoo Khay Chong,